Plant disturbance ecology the process and the response - Johnson, Edward A.; Miyanishi, Kiyoko (Academic Press, an imprint of Elsevier, 2021)
"Advances understanding of natural disturbances by combining geophysical and ecological processes. Provides a framework for collaboration between geophysical scientists and ecologists studying natural disturbances. Includes fully updated research with 5 new chapters and revision of 11 chapters from the first edition."--Provided by publisher.